(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The term catametabolism is here reintroduced and redefined in order to describe the post-embryonic development of diaspidid females. The three-stage scheme has been considered, until now, erroneously as neoteny. This stress the striking difference between catametabolism and neoteny as from the literature and from observation. Catametabolism is defined as a post-embryonic developmental scheme showing an early specialization through a morphological simplification; life cycle shortening is considered part of the catametabolic process indeed. The occurrence of catametabolism in all the known species of Diaspididae suggests that this term should be reported in the diagnosis of this taxon. The occurrence of neoteny and catametabolism in other Families of the Coccoidea is suggested.